The Abolition of the Death Penalty John Lazaro v United Republic of Tanzania (Application 003/2016) (2023) AfCHPR 335 (7 November 2023) (The Pretoria Student Law Review, 2025)
On 7 November 2023, the African Court on Human and Peoples’ Rights (‘the Court’) handed down judgment in a matter concerning the death penalty as a method of punishment in which South African Judge, Dumisa Buhle Ntsebeza and Congolese Judge, Blaise Tchikaya, provided dissenting opinions. The dissenting opinions characterised the death penalty as being inhumane, degrading, and a direct violation of Articles 4 and 5 of the African Charter on Human and Peoples’ Rights (‘the Charter’). The Honourable Judges further provided that the death penalty should be abolished in the legislation of the United Republic of Tanzania and that all member states of the African Union should collectively take progressive steps towards its abolition. This case discussion advances the dissenting opinions of Ntsebeza J and Tchikaya J, and further advocates for the abolition of the death penalty. The broader objective of this case discussion is to categorise the abolition of the death penalty as customary international law, meaning that even if there is no explicit rule of international law on its prohibition, courts in their interpretation can advance its abolition by adopting a human rights perspective.